Pilonidal Cyst of the Penis Mimicking Carcinoma - Luigi Cormio; Francesca Sanguedolce; Paolo Massenio; Giuseppe Di Fino; Giuseppe Carrieri (Case Reports in Urology)
Pilonidal sinus is a long-standing chronic inflammatory condition consisting of a sinus tract from the skin-lined orifice extending into subcutaneous tissue, with hairs attached to the wall of the tract and projecting outside of the opening. Penile location is rare, and differential diagnosis with severe balanoposthitis, epidermal cysts, and neoplasms can be difficult. We report a rare case of pilonidal cyst located between coronal sulcus and prepuce which, due to its ulcerated aspect and absence of a tract with projecting hairs, simulated a penile carcinoma.